Is it Created by AI?: An Experimental Investigation of Viewers’ Differentiation and Perceived Effectiveness of AI in Promoting a Non-profit Cause - Salerno, Emma; Salerno, Kate; Zhang, Ruonan (Politeknik Negeri Bandung, 2025)
The expeditious development of Generative Artificial Intelligence (AI) has allowed for an easier application of this technology in crafting communication campaigns. To investigate whether AI is helping or hindering the effectiveness of the communication process to persuade the public to act on a non-profit cause, a comparative experimental study is designed. Through a 2 (AI-generated vs. human-generated) x 3 (text only vs. text and image congruent vs. text and image incongruent) experimental research, we examined participants’ ability to differentiate between AI-generated content vs. human-generated content and their effects. Results from N = 700 participants sampled through Prolific.co indicated that participants could not differentiate between AI-generated and human-generated promotional text; however, they were able to differentiate between the images. Regarding effects, participants perceive human-generated content as more effective, authentic, trustworthy, and appealing through negative emotions, such as worry and anger. Although the study applied the Media Effects research framework through an experimental design, the findings are limited by the non-representative data collection through Prolific.co. The study provides empirical support for the application of generative AI in digital communication, internet marketing and advertising, and higher education in fields of promotional content generation. The study offers experimental support from the audience perspective to the conversation on the feasibility of AI applications in digital content generation in the fields of non-profit marketing and advertising.